DIGITAL MARKETING THROUGH CONTENT CREATORS: A PREREQUISITE FOR REVITALISING TOURISM LOCALLY AND INTERNATIONALLY - THE CASE OF “KHOUBAI” - Kerrouche Nawal, (International Journal of Innovative Technologies in Social Science, 2025)
Compared with its traditional counterpart, digital marketing represents a novel and distinct approach, operating within the digital sphere where interactions and practices unfold. Thus, it has become a vital outlet for institutions, particularly those active in the tourism and cultural sectors, regardless of their domain. Digital marketing offers a platform that saves time and enables broader outreach to local and international audiences. This is especially relevant given the presence of numerous pillars of tourism marketing, such as influencers and content creators, whose extensive follower bases have attracted the attention of institutions incorporating them into their marketing strategies. Given its significance, digital marketing has become an urgent necessity in our increasingly interconnected era, where economic development is often locally and globally driven by tourism.This research explores the key dimensions that digital marketing, through the inclusion of content creators, brings to the tourism sector. This study focuses on the Algerian content creator Khoubaib Kouas, known as "Khoubai”.